Fake news e o Ensino de História na Escola Dr. Antonio Jorge Dino, em São Luís - MA, entre os anos de 2018 e 2021 - Pimentel Junior, Francisco das Chagas Caldas (Universidade Federal do Tocantins, 2022)
This research problematizes fake news and historical awareness in the school environment, in the context of Escola Estadual Dr. Antônio Jorge Dino, located in the Jardim São Cristóvão neighborhood, in São Luís - MA. A form was applied via google classroom (2021), in the morning and afternoon shifts, making a total of 91, corresponding to the number of students enrolled. Of the total, 16 responded to the survey questionnaire, subsidy for this study. With this, we seek the participation of 3rd year high school students in discussions about fake news, commonly known as fake news, observing the implications involved in the production and circulation of this news and the impact on the way of seeing and being seen. in the group and in the community where they are inserted. In addition to the form and literature analysis, we will use the concepts of historical awareness and teaching history to understand how history, as a school subject, and the concept of historical awareness, developed from Rüsen (2008), can help our students. students and teachers at work on fake news in the classroom. For the development of the work, we will use as a theme some false news published on the social network Facebook between the years 2018 and 2021, which refer to vaccination. As an element of past/present articulation, we will briefly discuss the emergence and use of vaccines between the 19th and 20th centuries, presenting some considerations in order to problematize the Vaccine Revolt movement and the anti-vaccine movement verified from the pandemic. of Covid-19, between 2019 and 2021, in our present and daily lives. With this, the aim was to address a theme included in the curriculum guidelines of the state of Maranhão for the teaching of History, according to the curriculum guidelines booklet (2017). The final product is a didactic sequence.